2021
DOI: 10.1111/bjet.13073
|View full text |Cite
|
Sign up to set email alerts
|

A creative problem solving‐based flipped learning strategy for promoting students’ performing creativity, skills and tendencies of creative thinking and collaboration

Abstract: In most performing classes, such as dance or performing arts, students passively follow the scripts or demonstration provided by the teacher, and focus on imitating the acts and practicing repeatedly. Although researchers have begun trying out flipped learning to provide students with opportunities for self‐learning and to increase the time for in‐class collaborative learning and interactions, students’ performing creativity is generally ignored. As a result, the present study proposes a creative problem solvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 51 publications
3
21
0
2
Order By: Relevance
“…Chai et al ( 2020a ) examined the core dimensions of twenty-first century skills, and confirmed that collaborative learning predicts students' creative problem-solving. Hsia et al ( 2021 ) found that promoting collaborative learning and interaction in class could enhance students' creative thinking tendency. Our correlation test result matches their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Chai et al ( 2020a ) examined the core dimensions of twenty-first century skills, and confirmed that collaborative learning predicts students' creative problem-solving. Hsia et al ( 2021 ) found that promoting collaborative learning and interaction in class could enhance students' creative thinking tendency. Our correlation test result matches their findings.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zuo et al (2019) found that learners’ perceptions can influence their creativity. Flipped learning strategies and self-directed learning styles can enhance learners’ creative performance ( Hsia et al, 2021 ; Shafait et al, 2021 ). Again, studies have found a strong correlation between individual affective attitudes and creativity ( Silva and Coelho, 2019 ; Hernandez-Jorge et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study has several theoretical contributions. First, the main contribution is to the literature on creativity, where an amount of research argued that creativity is influenced by personality, Big Five factors, inspiration, training and learning, collaboration, information and communication technologies and psychology ( Stolaki and Economides, 2018 ; Huang, 2019 ; Lai et al, 2019 ; Liu et al, 2020 ; Hsia et al, 2021 ; Rahimi and Shute, 2021 ; Roth et al, 2021 ), but little attention is paid to the impact of emotions ( Falavarjani and Yeh, 2018 ). This study is one of the cutting-edge research to investigate how students in music education can deal with creativity to influence their performance.…”
Section: Discussionmentioning
confidence: 99%